Наративна стратегія автора авангардного роману - Філатова, Оксана; Filatova, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті на матеріалі експериментальних романів «Голяндія» Д. Бузька, «Пригоди Мак-Лейстера, Гаррі Руперта та інших» М. Йогансена, «Інтелігент» Л. Скрипника, «Золоті лисенята» Ю. Шпола розкрито особли¬вості наративної стратегії, що формувалася в умовах трансформації української літератури початку ХХ ст.Implementation of the plan of destruction of cultural codes of the national heritage by the Ukrainian futurists at the initial stage, and later approbation of the declared new categories of creativity are closely linked to an attempt to define the role of an artist not only as a violator of conventional conventions, but also as a generator of the spiritual freedom idea. The imperative of freedom in the communicative event released the writer from the immanent to the traditional literary paradigms cargo of didacticism and authoritarianism, and the reader – from the traditional perception of art composition and the formation of conventional sense. By initiating the maximum reformation of the reception process of literary product adherents of the New art also reject the installation at the psychological understanding of the author to the reader, which is denied as a settled sign of the «old art». The communication strategy of aesthetic subject and the recipient of a literary text defines the ideology of «ultra-self» (G. de Torre), it’s dominant is positioning the alternativity of subjective «I» to any «non-self».
The Narrative Strategy of the Author of an Avant-Garde Novel
Keywords: наративна стратегія; дискурс; комунікація; діалог; автор; авангардний роман; narrative strategies; discourse; communication; dialogue; author; avant-garde novel